التكنولوجيا - التغذية الراجعة عبر الوسائط في الكتابة باللغة الإنجليزية كلغة بين طلاب المرحلة »Grammarly« أجنبية: دراسة حول استخدام برنامج الجامعية الليبيين - الأثرم JUMAN SALEM (مجلة الاصالة, 2026)
Writing proficiency is often the most challenging task of linguistic competence, underlying many stages of planning, organization, and drafting; moreover, it demands precise control of grammar and vocabulary, a level of grammatical and structural precision that frequently eludes learners in traditional classroom settings. Despite its absolute importance, EFL learners continue to struggle to produce accurate written passages. This research is set to explore the impact of Written Automated Evaluation (AWE) in traditional Libyan classrooms, particularly Grammarly. Zhang and Hyland (2019) support the utilization of digital tools within classrooms, noting that learners who employed AWE performed significantly better and demonstrated grammatical accuracy, and furthermore, used a varied range of vocabulary, while projecting well-organized texts. The study adopted a mixed-methods approach. Samples of written assignments, semi-structured interviews, and a questionnaire were used. The data analysis reinforced the beneficial impact of AWE tools on both students and teachers. Grammarly enhanced students’ performance by creating an innovative environment and offering instant feedback; it offers the assistance that traditional methods lacked.